The impact of disease extent and severity detected by quantitative ultrasound analysis in the diagnosis and outcome of giant cell arteritis. (17th December 2019) - Monti, Sara; Ponte, Cristina; Pereira, Claudio; Manzoni, Federica; Klersy, Catherine; Rumi, Federica; Carrara, Greta; Hutchings, Andrew; Schmidt, Wolfgang A; Dasgupta, Bhaskar; Caporali, Roberto; Montecucco, Carlomaurizio; et al.
Abstract: Objectives: To develop a quantitative score based on colour duplex sonography (CDS) to predict the diagnosis and outcome of GCA. Methods: We selected patients with positive CDS and confirmed diagnosis of GCA recruited into the TA Biopsy (TAB) vs Ultrasound in Diagnosis of GCA (TABUL) study and in a validation, independent cohort. We fitted four CDS models including combinations of the following: number and distribution of halos at the TA branches, average and maximum intima–media thickness of TA and axillary arteries. We fitted four clinical/laboratory models. The combined CDS and clinical models were used to develop a score to predict risk of positive TAB and clinical outcome at 6 months. Results: We included 135 GCA patients from TABUL (female: 68%, age 73 (8) years) and 72 patients from the independent cohort (female: 46%, age 75 (7) years). The best-fitting CDS model for TAB used maximum intima–media thickness size and bilaterality of TA and axillary arteries' halos. The best-fitting clinical model included raised inflammatory markers, PMR, headache and ischaemic symptoms. By combining CDS and clinical models we derived a score to compute the probability of a positive TAB. Model discrimination was fair (area under the receiver operating characteristic curve 0.77, 95% CI: 0.68, 0.84). No significant association was found for prediction of clinical outcome at 6 months. Conclusion: A quantitative analysis of CDS and clinical characteristics is useful to identify patients with a positive biopsy, supporting the use of CDS as a surrogate tool to replace TAB. No predictive role was found for worse prognosis.